Faktor-Faktor Yang Mempengaruhi Customer Retention Di PT. Erafone Mega Mall Manado - Trecya S. M. Lompoliuw; Riane J. Pio; Roy F. Runtuwene (JURNAL ADMINISTRASI BISNIS, 2019)
The objective of this research was to Analyzing the variables of trust, commitment of communication and handling The complaint simultaneously and partially towards to customer retention of mobile products and most dominant variables of trust, commitment, communication and handling The complaint in influencing customer retention at PT Erafone Mega Mall. Where companies must be able to have strategies in attracting and retaining customers such as relationship marketing strategies that have 4 variables, namely : trust, commitment, communication and secure of complaints. When a company is able to carry out that strategy well, consumers will feel satisfied and comfortable with the sold products and services provided by the company to consumers and when it goes well, it is likely that consumers will buy again and can recommend products from the company. - This type of research is a type of descriptive research verification. The data collection technique in this study used questionnaire and literature. To examine the effect of customer retention on customer satisfaction by using multiple linear regression test analysis techniques. The tools used in the test instrument data are validity and reliability test, assumption test (normality test, multicellularity test and heteroscedasticity test). The results of this study indicate that the four independent variables have a significant and simultaneous effect on customer retention. While the most dominant influence on customer retention is customer trust in using PT ERAFONE Manado products.